Updated description of the adult male of Kuwania bipora Borchsenius (Hemiptera: Coccomorpha: Kuwaniidae) with a discussion on the relationships of Kuwania with some other archaeococcoid genera - Zheng, Xinyi; Wu, San’an (Zootaxa, 2022)
The genus Kuwania Cockerell in Fernald 1903 (Hemiptera: Coccomorpha: Kuwaniidae) contains seven species worldwide. The only species in the genus for which the adult male has been described is Kuwania bipora Borchsenius 1960, but the description and illustration are inadequate to clarify taxonomic relationships. This paper describes and illustrates the adult male of K. bipora to modern standards. The relationship of Kuwania to three other archaeococcoid genera, based on the male morphology, is discussed; the morphology of the adult male of Kuwania is closest to that of Neosteingelia Morrison 1927.